If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 27 = 5x + -9 Reorder the terms: 27 + 2x = 5x + -9 Reorder the terms: 27 + 2x = -9 + 5x Solving 27 + 2x = -9 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 27 + 2x + -5x = -9 + 5x + -5x Combine like terms: 2x + -5x = -3x 27 + -3x = -9 + 5x + -5x Combine like terms: 5x + -5x = 0 27 + -3x = -9 + 0 27 + -3x = -9 Add '-27' to each side of the equation. 27 + -27 + -3x = -9 + -27 Combine like terms: 27 + -27 = 0 0 + -3x = -9 + -27 -3x = -9 + -27 Combine like terms: -9 + -27 = -36 -3x = -36 Divide each side by '-3'. x = 12 Simplifying x = 12
| s-2=31 | | 8(3n-2)=(6n+2)+4 | | -18-4x=6-8x | | 174-4x=23x+18 | | 8a+5a+5b-3b= | | 2x+20=9x-27 | | -16=0.2n | | 3/5=6 | | 122-3x=15x+24 | | 5(3x+1)=4x-8x | | 1+4m+5m^2+2m^3=0 | | 1-3+7=6 | | 5u-10v= | | 12-9x=35-16x | | x^3-9x^2+24x+1=0 | | 4+3*5=x | | 4x-x-2=34 | | 3bc=12+9bc | | s+808=57 | | -(7-4x)=7 | | 114=2u | | f29=7 | | 11x+11=4x+158 | | 42+5x=9-8x | | v+66=993 | | 6*8=0 | | 284-7x=38x+24 | | 7x+2x-3=5x+9 | | q+407=73 | | -19x-21=35-x | | xy=29 | | 20x^2+60x+45=0 |